Research Progress in Sodium Reduction Strategies for Plant-Based Meat Products - WANG Rui, PENG Yu, SHAN Ziming, LI Mo, WEN Xin, NI Yuanying (Shipin Kexue)
With the exacerbation of relevant issues such as population growth and environmental deterioration, the adverse impact of traditional livestock farming is gradually becoming prominent, while the market for plant-based meat products is expanding. Numerous studies have focused on improving the quality of plant-based meat products in terms of appearance, texture, taste and flavor to make them more similar to real meat. However, plant-based meat products on the market generally contain high sodium levels, which contradicts the concept of healthy diet and seriously affects the nutritional value and promotion of plant-based meat products. Therefore, this article starts with an overview of the development of plant-based meat products, analyzes the current status and causes of high sodium levels in related products, and focuses on the salt and sodium reduction strategies used in the production of plant-based meat in the three aspects of texture and flavor shaping, fiber structure construction and raw material preparation, with a view to reducing the sodium content without affecting the sensory quality of plant-based meat products in order to produce and promote healthier low-sodium plant-based meat products.